(3eLehY COHjs - (3eLghds
(3ChdgG (B:s
(3hbGd GdTjN Ydj GdeGNhSj gPG GdTYQ(B: (3YGQVj hGdQCS TGH hGdUHG hdi hZGH s
(3BNQgG (B:s
(3ef bUjOI QGFjI NJGegG bhdg(B: (3Ke GdUdGI Ydi GdfHj eMeOkG ecj MLGRj SjOkG eNJGQ s
(3HgG fXGe GdJYbjHIs
(3TYQ h fKQ d(B:(3Ydj GdeGNhSj(B, (3h jhSa Hf SdeGf(B, (3h OjhGf CHj fhGS h ZjQges
(3ajgG TYQ fHWjs
(3cJH SfI (B1063 (3h (B1064 s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
Keywords: (3GdCOHs